THE PHARMACEUTICAL SECTOR IN SERBIA’S BIOECONOMY: EVIDENCE FROM THE AGRI-FOOD VALUE CHAIN - Adamović, Miljan; Hodžić, Azra; Kazanović, Radmila; Delić-Ćustendil, Sunita (Economics of Agriculture, 2026)
The aim of the paper is to analyse the pharmaceutical sectorin the Republic of Serbia’s agro-based production systemthrough a comparative analysis with the food industry overthe period 2016–2024. The analysis relies on aggregatedsectoral financial data and uses various financial indicators.The findings show that the pharmaceutical sectorconsistently achieves higher value added, stronger exportorientation, faster long-term growth dynamics, and morestable performance than the food industry. This confirmsthe existence of a pronounced structural gap withinSerbia’s bio-economy between traditional agro-industrialsectors and knowledge-intensive bio-based industries. Thefindings provide a quantitative basis for assessing the roleof the pharmaceutical sector as a carrier of higher valueadded stages in the agro-based production system.